Effect of thiophene linker addition to fluorene-benzotriazole polymers with the purpose of achieving white emission in OLEDs - Kok, Cansu; Doyranli, Ceylan; Canimkurbey, Betul; Mucur, Selin Piravadili; Koyuncu, Sermet (ROYAL SOC CHEMISTRY, 2020)
With the purpose of obtaining white emission from single layer organic light emitting diodes (OLEDs), fluorene benzotriazole based polymers with double bond subunits (namely TP2 and SP3 with and without thiophene linker, respectively) were synthesized by a Suzuki cross-coupling polymerization reaction. SP3 and TP2 were used as an emissive layer of the OLED devices due to their outstanding solubility in organic solvents, photoluminescence intensity and morphological suitability for fine thin film-forming capability. The optical, electrochemical, light emission and electroluminescence characteristics, Density Functional Theory (DFT) calculations and admittance spectroscopic analysis of OLEDs based on SP3 and TP2 were realized in detail to understand the effects of thiophene linker addition as a donor unit to the main chain of fluorene benzotriazole based polymers. As a result, TP2 emitted a bright yellow emission with a maximum brightness of 243 cd m(-2) at 40 mA cm(-2), and a maximum current efficiency of 1.38 cd A(-1) with more broad electroluminescence characteristics than SP3 polymer without the thiophene linker. SP3 emitted a greenish yellow emission with a maximum brightness of 1001 cd m(-2) at 845 mA cm(-2), and a maximum current efficiency of 0.33 cd A(-1). Carrier transport properties, charge carrier transit time and the equivalent circuit modelling studies were obtained through admittance spectroscopy. An equivalent circuit model with a combination of two resistors and one capacitor explained the charge conduction mechanism of SP3 and TP2 based OLEDs. SP3 and TP2 OLED devices represented typical p-type transporting characteristics with mobilities of 0.073 and 0.017 cm(2) V-1 s(-1), respectively with simplified device configuration. All the results indicate that thiophene addition to the main chain of fluorene benzotriazole based polymers with double bond subunits lead to a promising candidate for white emissive materials used in single layer white OLEDs.
Keywords: SOLUTION PROCESSABLE BENZOTRIAZOLE; SOLAR-CELLS; COPOLYMERS; POLYACETYLENE; DERIVATIVES; INJECTION; Chemistry